NEW RECORD OF Cyrtodactylus cattienensis Geissler, Nazarov, Orlov, Bohme, Phung, Nguyen & Ziegler, 2009 (Squamata: Sauria: Gekkonidae) IN NUI ONG NATURE RESERVE, BINH THUAN PROVINCE, VIETNAM - Ngoc Thao, Hoang; Thanh Tay, Tran; Thi Quy, Le; Thi Hong Lam, Le; Xuan Quang, Hoang (Journal of Forestry Science and Technology, 2022)
Cyrtodactylus cattienensis was discovered in Dong Nai and Ba Ria - Vung Tau provinces by Geissler et al. (2009). Some other locations of this species were also discovered in later studies. We provide a new record for this species from Binh Thuan province based on three specimens collected in Nui Ong Nature Reserve. Data on the morphological of the collected specimens are also provided. Specimens include combination characters: tubercles present on the head, body, limbs and tails; 28 - 47 interorbital scale rows; 19 tubercules rows belonging at midbody; 35 - 38 ventral scales smooth, medial scales three times larger than the dorsal granules, lateral folds absent; males with 6 - 7 precloacal pores in angular continuous series, males and female with 17 -18 (including precloacal pores scales) enlarged scales in the precloacal region, 5 - 7 enlarged femoral scales on each side, femoral pores absent; subcaudal scales are small, not transversely enlarged; there are 15 - 16 lamellas under the fourth finger and 17 - 20 lamellas under the fourth toe. Results of the research also show that the distribution characteristic of Cyrtodactylus cattienensis is larger than most species of the Cyrtodactylus genus, which species nearly discovered in Vietnam. The new record also extends the distribution of this species about 60 km (from Cat Tien National Park to Nui Ong Nature Reserve).